Penicillin-Binding Proteins in the Pathogenic Intestinal Spirochete Brachyspira pilosicoli - Dassanayake, Rohana P. (American Society for Microbiology, 2005)
Penicillin-binding proteins (PBPs) of slightly different molecular masses (94, 62 or 68, 42 or 50, 25, and 22 kDa) were identified in one human and two porcine Brachyspira pilosicoli strains. Identification of PBPs of B. pilosicoli provides a basis for characterization of the genes encoding these proteins among pathogenic intestinal spirochetes of humans and animals.